Demodex prevalence in mine, textile and food factory workers with dermatosis: a cross-sectional, multicenter study - Metin, Zuhal; Akca, Hanife Merve; Ozkoca, Defne; Imren, Isil Gogem; Durmaz, Koray; Kara, Kevser Tuncer; Ozyurt, Kemal (Springer, 2023)
Demodex, a type of mite, lives in human hair follicles. They can multiply very quickly in some conditions and then start to irritate the skin by causing skin disorders. This study aims to investigate if working environment conditions affect the prevalence of Demodex. A cross-sectional, multicenter study was conducted with three different occupational groups: mine, textile and food factory workers (n = 102). Determined industry workers who applied to our outpatient dermatology clinics with the complaint of dermatosis in three different cities were included in the study. Demodex positivity was checked by dermoscopy. Differences between categorical variables examined with Chi-square analysis and T test was used to compare continuous variables between groups. 50% Demodex positivity was found in mine workers, 45.3% in food factory workers and 66.7% in textile manufacturing workers. A high rate of Demodex positivity was observed in all three occupational groups. Although the highest positivity rate was observed in textile manufacturing workers, no significant difference was found between the groups (p = 0.320). The overall prevalence of Demodex in female workers was statistically significantly higher than in male workers (p = 0.029). Exposure of workers to a wide variety of factors in work environments such as textile factories and the fact that women are more sensitive to external factors may have caused the prevalence of Demodex to be higher in these groups. So, a change in the work environment or the use of suitable protective equipment may benefit the treatment of diseases caused by Demodex. But, further studies are needed with larger and various industry groups to make more certain views.
Keywords: Demodex; Dermatosis; Miner; Textile manufacturing; Food factory; Skin health